ChemInform Abstract: An Efficient Synthesis of Styrenyl Enamides from 4‐Aryl‐2‐oxazolidinones in the Presence of Strong Base. Issue 6 (21st January 2016) - Zou, Kaihe; Ye, Jinxing; Wu, Xin‐Yan
Abstract: Starting from 4‐aryl substituted 2‐oxazolidinones, 2‐thioxooxazolidines or 2‐thioxothiazolidines a convenient method for the preparation of various N‐acyl styrenyl enamides is developed.